2021
DOI: 10.1039/d0cb00171f
|View full text |Cite
|
Sign up to set email alerts
|

Substrate inhibition by the blockage of product release and its control by tunnel engineering

Abstract: Substrate inhibition can be caused by substrate binding to the enzyme–product complex and can be controlled rationally by targeting enzyme access tunnels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 53 publications
1
34
0
Order By: Relevance
“…Previous studies indicated that the characteristics of substrate access tunnels can have a decisive influence on enzyme–substrate specificity and activity. In t-PlaF, we focused on T1 and T2 because only these two allow direct access of GPL or LGPL substrates from the membrane in the t-PlaF A configuration. In contrast, to enter into T3, substrates would need to pass through the solvent, which is energetically unfavorable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the characteristics of substrate access tunnels can have a decisive influence on enzyme–substrate specificity and activity. In t-PlaF, we focused on T1 and T2 because only these two allow direct access of GPL or LGPL substrates from the membrane in the t-PlaF A configuration. In contrast, to enter into T3, substrates would need to pass through the solvent, which is energetically unfavorable.…”
Section: Discussionmentioning
confidence: 99%
“…The work also calls for further ITC studies on enzyme variants for fundamental studies to identify the involvement of positions of interest on reaction component binding or conversion . Finally, molecular modeling of the binding of reaction components can provide atomistic insights into binding processes. Because our approach is amenable to automation and scale-up for high-throughput, the combination of such diverse approaches will provide the high-quality data needed for the engineering of enzymes and biocatalytic processes through machine learning to speed up the future development of industrial biocatalysis. , …”
Section: Discussionmentioning
confidence: 99%
“…59 Finally, molecular modelling of the binding of reactants can provide atomistic insight into binding processes. [60][61][62][63] Because our approach is amenable to automation and scale-up for high-throughput, the combination of such diverse approaches will provide the high-quality data needed for the engineering of enzymes and biocatalytic processes through machine learning to speed up the future development of industrial biocatalysis. 1,[64][65][66][67]…”
Section: Discussionmentioning
confidence: 99%